1993
DOI: 10.1002/ptr.2650070123
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oils of different samples of Thymus baeticus boiss

Abstract: Gas chromatography was used to determine the chemical composition of the essential oil of female and hermaphrodite Thymus heticus Boiss. collected in Ugijar (province of Granada, Spain). The results were compared with the chemical composition of other samples of the same species, collected in Lanjar6n. These comparisons showed some qualitative Merences, and more obvious quantitative diflerences, in the compositions of the essential oils. We also investigated the antimicrobial activity of all samples. This acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…(Baser, Kirimer, Ermin, K€ urkc ߀ uoglu, & T€ umen, 1996;Cosentino et al, 1999;Moldão-Martins, Bernardo-Gil, Beirão da Costa, & Rouzet, 1999;Ruiz et al, 1993;S aez, 1995). In some cases, two different varieties displayed the same essential oil yield and quality, although the plants were morphologically different, whereas three chemotypes were detected in the same population of plants with the same morphological characteristics Tzakou, Verykokidou, Roussis, & Chinou, 1998).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 98%
“…(Baser, Kirimer, Ermin, K€ urkc ߀ uoglu, & T€ umen, 1996;Cosentino et al, 1999;Moldão-Martins, Bernardo-Gil, Beirão da Costa, & Rouzet, 1999;Ruiz et al, 1993;S aez, 1995). In some cases, two different varieties displayed the same essential oil yield and quality, although the plants were morphologically different, whereas three chemotypes were detected in the same population of plants with the same morphological characteristics Tzakou, Verykokidou, Roussis, & Chinou, 1998).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 98%
“…The three major identified compounds were trans-geraniol (63.46%), geranyl acetate (28.83%) and in a lower concentration trans-caryophyllene (2.51%). Since they have been previously reported as antimicrobial (Scortichini and Rossi, 1991;Cruz et al, 1993;Pattnaik et al, 1997;Douglas et al, 2004;Mimica-Dukic et al, 2004) commercial samples of them were tested against one ETEC and one EPEC serotypes. Results showed ( Table 4) that geraniol possessed the best antimicrobial activity (MICs = 20 and 8 g/mL) being EPEC serotype the most susceptible species (MIC = 8 g/mL).…”
Section: Chemical Composition Of the Cymbopogon Martinii Essential Oilmentioning
confidence: 99%
“…A number of studies have shown that some genus belong to the Lamiaceae family such as Thymus and Satureja, due to possess phenolic monoterpenes like carvacrol, thymol, α-pinene, and p-cymene have high antifungal effects against phytopathogenic fungi (Cruz et al, 1993;Mohammadi, Nazari, Imani, & Amrollahi, 2014;Sko cibušić, Bezić, & Dunkić, 2006;Villa & Veiga-Crespo, 2014).…”
Section: Introductionmentioning
confidence: 99%